Public beliefs and willingness to accept COVID-19 vaccines among adults in South-Western Nigeria: A cross-sectional study - Itse Olaoye; Aniebet Ekong; Abiona Samuel; Eirini Kelaiditi; Kyriaki Myrissa; Tsemaye Jacdonmi; Famokun Gboyega (AIMS Public Health, 2023)
Background: Despite the government's and development partners' unmatched efforts to ensure that every eligible person receives vaccinations, there have been concerns about vaccine fear, government mistrust, vaccine hesitancy and rejection expressed by the public, as well as various conspiracy theories involving the COVID-19 vaccines. This study assessed the public beliefs and willingness to accept COVID-19 vaccines and related factors among residents of Ondo State, Nigeria.